Kewenangan Lembaga Pengkajian Pangan, Obat-obatan, dan Kosmetika - Majelis Ulama Indonesia Pasca Berlakunya UU No. 33 tahun 2014 Tentang Jaminan Produk Halal - Ade Septiawan; Ahmad Mukri Aji (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2016)
Abstract: This study aims to determine the authority of LPPOM in establishing halal products after the enactment of Law no. 33 Year 2014. Based on the research results, it is concluded that there has been a change of authority of LPPOM MUI before and after the coming into effect of Law no. 33 year 2014. For 23 years since its establishment, LPPOM MUI has full authority over the establishment of halal certification, but post-birth and enactment of Law no. 33 of 2014, it no longer has full rights to the expenditure and certification of the guarantee of halal products, but only as partners. The need for halal certification or halal label is very needed in Indonesia. Especially the common people and especially the Muslim community in Indonesia, because with the availability of guaranteed halal food products, at least Muslim consumers no longer worry about the existence of a mixture of materials containing harmful substances are prohibited, both legally and religiously.Keywords: Authority, LPPOM MUI, and halal certification. Abstrak: Penelitian ini bertujuan untuk mengetahui wewenang LPPOM dalam penetapan produk halal pasca berlakunya UU No.33 Tahun 2014.Berdasakan hasil penelitian maka diperoleh kesimpulan bahwa terjadi perubahan wewenang LPPOM MUI sebelum dan sesudah berlakunya UU No.33 Tahun 2014. Selama 23 tahunsemenjak berdirinya, LPPOM MUI berwenang penuh atas penetapan sertifikasi halal, namun pasca lahir dan berlakunya Undang-Undang No.33 Tahun 2014, ia tidak lagi memiliki hak penuh atas pengeluaran dan penetapan sertifikasi jaminan produk halal, melainkan hanya sebagai mitra. Kebutuhan sertifikasi halal atau label halal memang sangat dibutuhkan di Indonesia. Terlebih masyarakat awam dan khususnya masyarakat muslim di Indonesia, karena dengan tersedianya jaminan produk makanan halal, setidaknya konsumen muslim tidak lagi khawatir akan adanya campuran bahan-bahan yang mengandung zat berbahaya yang dilarang, baik secara hukum negara maupun agama. Kata kunci:Kewenangan, LPPOM MUI, dan sertifikasi halal.